Linguistic Features and Translation of English Sports News - Zhang, Hongmei (Pacific International Journal, 2024)
Abstract Sports, as one symbol of social civilization, are indispensable to our social and cultural life. Nowadays, with the development of society and the economy, sports news occupies a significant place in our daily lives and has aroused people’s attention. English sports news, as a kind of special news style, has the characteristics of news style but also presents its unique language features. This paper tries to analyze the linguistic features of English sports news with vivid examples of vocabulary and sentences. It includes five parts. The first part introduces the origin and development of English sports news. The second is the literature review, which introduces previous studies on English Sports News and its translation. Then, the third and fourth parts study the linguistic features and translation of English sports news with vivid examples. Lastly, the fifth part is the conclusion, which summarizes the linguistic features of English Sports News and gives several translation principles. For instance: faithfulness, expressiveness, and elegance; literal translation, and free translation. Keywords: English sports news; linguistic features; translation methods